Quantum information with semiconductor nanostructures - Adrados, C. (2017)
Integrated optoelectronic devices based on exciton-polaritons are very promising for quantum information, since they allow quantum optical effects as well as spin control and spin switching. Moreover the quantum fluid properties of exciton polaritons indicate that they are good candidates for quantum simulation.